EVALUATION OF THE INDONESIAN PEARL AND PEARL OYSTER MARKET - Raismin Kotta; Irzal Effendi; Iis Diatin; Tatag Budiardi (Indonesian Aquaculture Journal, 2026)
Evaluation of the Indonesian pearl market is still dominated by trade analysis, while integration of export data with field information on supply chains and market dynamics has been limited. This study aims to evaluate the pearl and pearl oyster (Pinctada maxima) market in Indonesia through an analysis of export trends, changes in trade value, and supply chain conditions during the 2020–2024 period. The study used a survey method approach with primary data collection through field observations and in-depth interviews with 45 respondents consisting of cultivators, traders, and consumers in North Lombok, East Lombok, and West Sumbawa, supported by secondary data from government agencies and the Indonesian Pearl Cultivation Association. The analysis was conducted descriptively using Microsoft Excel and SPSS. The results show that the total volume of Indonesian pearl exports during the observation period reached 46,072 kg with an export value of approximately USD 309.8 million. Although export volume decreased in 2023–2024, export value increased significantly in 2023 to USD 112.9 million, indicating an increase in average prices or a shift towards higher value-added products. Interview findings and field observations revealed that product quality, premium market preferences, and challenges in the supply chain and international marketing standards were the main factors influencing export performance. It was concluded that the competitiveness of the Indonesian pearl market is supported by increasing product value, but supply chain strengthening, quality standardization, and sustainable marketing strategies are still needed to maintain export growth.